A comparative study on total phenolic content, reducing power and free radical scavenging activity of aerial parts of Barleria prionitis - Sunil K. Jaiswal,; Mukesh K. Dubey,; Sanjeeb Das,; Arti Raj Verma,; Ch.V. Rao, (International Journal of Phytomedicine, 2010)
Context: Barleria prionitis L. (Family Acanthaceae; commonly known as Vajradanti), is an annual shrub, 1–3 feet high, found throughout tropical Asia and in South Africa. Objective: The aim of the present study was to evaluate the antioxidant activity of 50% ethanolic extract of leaf, flower, and stem of B. prionitis by using β carotene bleaching assay, reducing power and free radical scavenging activity (DPPH and hydroxyl radical scavenging activity). Total phenolic content (TPC) was analysed by the Folin–Ciocalteu colorimetric method using gallic acid as standard and expressed as mg/g gallic acid equivalent (GAE). Results: Total phenolic content (TPC) and antioxidant activity (AOA) in B. prionitis leaves were found to be 67.48 mg/g GAE dry plant material and 79.20%. The B. prionitis leaves exhibited strong free radical scavenging activity as evidenced by the low IC50 values in both DPPH (1,1-diphenyl-2-picryl hydrazyl) (336.15 μg/ml) and hydroxyl radical (568.65 μg/ml) methods. Conclusions: The leaf of B. prionitis possesses high phenolic content, potential antioxidant activity, reducing power & radical scavenging activity in comparison to flower and stem.